CAPITALIZATION OF RELATIONS IN THE CONTEXT OF VALUE MANAGEMENT - G. Serebryakova (Вестник университета)
The article deals with the capitalization of relations as a result of the interaction under conditions of value management. The author proves that, at the present time to obtain high results organizations form capital, contributing to sustainable socio-economic systems.